Perjuangan Seorang Ibu dalam Puisi Kukusan Karya Emi Suy dan Puisi Bunda Airmata Karya MH Ainun Najib: Kajian Sastra Bandingan - Maulida Laily Kusuma Wati; Teguh Supriyanto; Agus Nuryatin (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2024)
This research aims to determine the relationship between the poem Kukusan by Emi Suy and the poem Bunda Airmata by MH Ainun Najib. The theory used in this research uses comparative literary theory which discusses metaphor, symbols and relevance in the two poems. The data collection technique uses first level semiotic reading, namely heuristics. The data analysis technique uses the second level of semiotic reading, namely hermeneutics. The results of the analysis of the poem